Impact of prior flavivirus vaccination on immunogenicity and efficacy of an inactivated Zika vaccine in Indian rhesus macaques. Issue 19 (5th May 2023) - Young, Ginger; Zahralban-Steele, Melissa; Dean, Hansi J.
Abstract: Flaviviruses are antigenically related. We evaluated the immunogenicity and efficacy of Takeda's purified inactivated Zika vaccine (PIZV) candidate in macaques previously vaccinated with several commercially available heterologous flavivirus vaccines. Heterologous flavivirus vaccination did not elicit Zika virus (ZIKV) neutralizing antibodies and did not impact neutralizing antibody titers after one dose of PIZV. After a second PIZV dose previous vaccination with flavivirus vaccines had variable impact on ZIKV neutralizing antibody titers. However, all macaques were protected against viremia after Zika virus challenge 8–12 months post-PIZV vaccination. Therefore, vaccine-induced immunity against heterologous flavivirus vaccines does not impact PIZV efficacy in macaques.